THE INFLUENCE OF INSTAGRAM ACCOUNT @REPUBLIKAONLINE TOWARD THE FULLFILLMENT OF INFORMATION NEEDS FOR MUSLIM MILLENIAL - Andini Nur Bahri; Ahmad Zueni (An Nadwah, 2021)
This study aims to find out the influence of the @republikaonline Instagram account has on meeting the online information needs of the Muslim millennial generation. This study uses a quantitative approach, which is a search or use of data in the form of numbers as a tool to analyze information or events that by using simple linear regression analysis which aims to analyze the magnitude of the influence of the independent variable on the dependent variable. The sample is 100 North Sumatra State Islamic University students who are followers of the @republikaonline Instagram account. Based on the results of the study, the significance value is smaller than 0.05 (0.000 <0.05), so it can be concluded that the X variable has a very significant influence on the Y variable.